An Analysis of the Study of Home Industry Business Feasibility - Safa’atillah, Nurus; Handayati, Ratna (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
The background to this research is that the home industry is developing rapidly, but is not yet optimal. This research aims to analyze a business feasibility study in Wedoro sandals to help boost the production and sales of Wedoro Sidoarjo sandals. This research method used descriptive qualitative analysis using several aspects of business feasibility studies which are used as research indicators to calculate the level of business feasibility from all aspects of business feasibility. The result of this study is the production of shoes and sandals from Wedoro Village began to decrease not optimally. Another factor that caused sales turnover to fall was the entry of shoes and sandals from China which were sold in the domestic market at lower prices and better quality. So it has the effect of decreasing the sales turnover of Wedoro sandals. So, it can be said that the Wedoro shoes and sandals business is not feasible in marketing analysis.